A fuel cell membrane electrode catalyst layer slurry and a method for preparing the same
Patent Information
- Application Number
- CN202610947568.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]本发明的目的在于克服现有技术的不足,提供一种燃料电池膜电极催化层浆料的制备方法,旨在解决现有方法中离聚物与催化剂混合不均、分散稳定性差以及催化层离子传输效率低的问题
1、抑制离聚物过度竞争吸附:通过将溶剂预先混合均匀后按不同比例分成两份,分别用于预分散催化剂和离聚物,确保两份分散液的溶剂环境完全一致。使离聚物在混合前已预先在最终溶剂体系中舒展、解缠结,避免其在催化剂分散初期大量接触催化剂表面,从而抑制了离聚物在催化剂外表面的不均匀包覆,有利于形成更均匀的离子传输网络。
Smart Images

Figure CN122907653A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of fuel cell technology, specifically relating to a fuel cell membrane electrode catalytic layer slurry and its preparation method. Background Technology
[0002] The catalyst layer of a proton exchange membrane fuel cell (PEMFC) is the core site of electrochemical reactions, and its microstructure directly affects the cell's performance and lifespan. The catalyst layer typically consists of a catalyst (such as Pt / C), ionomers (such as perfluorosulfonic acid ionomers), and a solvent system. The preparation of the catalyst layer slurry is a crucial step in the catalyst layer preparation process. The dispersion state, agglomeration degree, and interactions of the catalyst and ionomers in the slurry directly affect the microstructure of the catalyst layer (such as porosity, ionomer distribution, and catalyst utilization) and the final cell performance.
[0003] In existing technologies, the preparation method of catalyst layer slurry often employs a "one-pot" method, where all components are added and mixed simultaneously or sequentially. Patent application CN121662835A discloses a fuel cell catalyst layer and its preparation method, wherein the catalyst layer slurry is prepared by ball milling and degassing Pt / C catalyst, perfluorosulfonic acid resin, water, tetrahydropyran, and an organic alcohol solvent. However, due to the strong interaction between ionomers and the catalyst surface, in one-step mixing or sequential addition methods, ionomers are prone to preferentially adsorbing onto macropores or defect sites on the catalyst surface, resulting in uneven ionomer distribution. Some catalyst particles lose active sites due to over-coating, i.e., poisoning; while in other areas, proton conduction is hindered due to insufficient ionomers. This leads to poor distribution of the three-phase reaction interface in the catalyst layer, increased ion transport resistance, and ultimately affects battery performance.
[0004] To improve dispersion, some existing technologies attempt to adjust the solvent ratio or employ multi-step addition, first dispersing the catalyst in one solvent and the ionomer in another before mixing. Patent CN116454290B discloses a self-humidifying fuel cell membrane electrode and its preparation method. The method for preparing the catalyst layer slurry involves first mixing the catalyst and ultrapure water uniformly, then dispersing them at high speed using shearing to form a first slurry; then weighing and mixing nano-zirconia, sulfonated zirconia, the ionomer solution, ultrapure water, and isopropanol, followed by dispersion using ball milling, shearing, and homogenization to form a second slurry; finally, the first and second slurries are mixed and dispersed to form the catalyst layer slurry. However, this method often results in conformational changes in the ionomer chains or abrupt changes in the catalyst surface energy during mixing due to differences in the two solvent systems (such as polarity and surface tension), failing to effectively control the uniform adsorption of the ionomer on the catalyst surface. Therefore, developing a preparation method that can optimize the interfacial compatibility between the catalyst and the ionomer, effectively control the distribution of the ionomer, improve the catalyst utilization rate, and improve the stability of the slurry has important practical value. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a method for preparing a catalyst slurry for a fuel cell membrane electrode assembly (MEA). This method aims to solve the problems of uneven mixing of ionomers and catalysts, poor dispersion stability, and low ion transport efficiency in existing methods. The method involves pre-mixing a mixed solvent and then uniformly dividing it into portions, which are used separately to pre-disperse the catalyst and ionomer. This ensures that both reach their optimal initial dispersion state in the same solvent environment before mixing. This significantly improves the uniformity and stability of the slurry, reduces excessive coverage of the catalyst's active sites by the ionomer, and ultimately forms a catalyst layer with a uniform structure and excellent electrochemical performance.
[0006] This invention first provides a method for preparing a catalyst layer slurry for a fuel cell membrane electrode, comprising the following steps: Step 1: Prepare a mixed solvent system; Step 2: Divide the mixed solvent system obtained in Step 1 into a first mixed solvent and a second mixed solvent by mass ratio; Step 3: Add the platinum-based catalyst to the first mixed solvent described in Step 2 and perform a first dispersion treatment to obtain a catalyst dispersion. Step 4: Add the ionomer to the second mixed solvent described in Step 2 and perform a second dispersion treatment to obtain an ionomer dispersion. Step 5: Under stirring conditions, add the ionomer dispersion obtained in step 4 to the catalyst dispersion obtained in step 3, mix evenly, and obtain a premixed slurry. Step 6: The premixed slurry obtained in step 5 is subjected to high-speed shear dispersion treatment to obtain the fuel cell membrane electrode catalyst layer slurry.
[0007] In some embodiments, in step 1, deionized water and alcohol solvent are mixed at a mass ratio of 1:3 to 5:1 to obtain a mixed solvent system; the alcohol solvent is selected from one or more of ethanol, isopropanol, and n-propanol with suitable dielectric constant and surface tension, which can effectively wet the carbon-supported platinum catalyst with both hydrophilic and hydrophobic properties, and can also be well compatible with perfluorosulfonic acid ionomer, thereby effectively dispersing the catalyst.
[0008] In some embodiments, the mass ratio of the first mixed solvent to the second mixed solvent in step 2 is 1:1 to 1:3. The first solvent needs to be sufficient to fully wet and disperse the catalyst particles (a higher mass ratio is beneficial to reduce solid content and reduce agglomeration), while the second solvent needs to ensure that the ionomer molecular chains are fully extended and do not entangle (a lower ratio will result in local over-concentration of the ionomer, which is not conducive to uniform coating).
[0009] Preferably, the platinum-based catalyst in step 3 is a platinum-carbon catalyst, wherein the platinum mass ratio is 40%~70%.
[0010] More preferably, the platinum-carbon catalyst is a platinum-carbon catalyst with a platinum mass ratio of 60%.
[0011] Preferably, the ionomer described in step 4 is a perfluorosulfonic acid resin. Perfluorosulfonic acid resin can be purchased directly, usually as a solution, with a mass ratio of 5% to 25%, and the solvent is mostly ethanol, isopropanol, or n-propanol.
[0012] Preferably, it is a perfluorosulfonic acid resin solution with a mass ratio of 20%.
[0013] In some embodiments, the amount of ionomer solution added is such that the mass ratio of the dry weight of the ionomer in the final slurry to the mass of the carbon support in the catalyst is 0.8:1 to 1.2:1.
[0014] In some embodiments, step 3, the first dispersion treatment, employs ultrasonic dispersion for 10-30 minutes at a temperature of 5-25°C to ensure thorough and uniform dispersion; step 4, the second dispersion treatment, also employs ultrasonic dispersion for 10-30 minutes at a temperature of 5-25°C to ensure thorough and uniform dispersion. Low-temperature control is used to suppress solvent evaporation and localized overheating during the dispersion process, prevent catalyst surface oxidation or ionomer degradation, and ensure that both processes achieve optimal initial dispersion in the same solvent environment.
[0015] In some embodiments, the stirring conditions in step 5 are magnetic stirring at a speed of 500 rpm to ensure thorough and uniform mixing.
[0016] In some embodiments, the ionomer dispersion in step 5 is added dropwise or all at once; the time for uniform mixing is 10-60 minutes to ensure initial homogeneity.
[0017] Preferably, step 5 involves adding the ionomer dispersion dropwise, which allows for better control of the ionomer's dispersion state and avoids agglomeration.
[0018] Specifically, the high-speed shear dispersion in step 6 uses a high-speed shear disperser with a shear linear velocity of 10~25 m / s and a processing time of 30~60 min. During the dispersion process, the slurry is cooled and the slurry temperature is controlled at 5~10℃ to achieve final fine dispersion. This step breaks up weak agglomerates through strong shear force, while low-temperature cooling prevents the denaturation of ionomers caused by high shear heat generation, thereby forming a submicron-level uniform slurry.
[0019] The present invention also provides a fuel cell membrane electrode catalytic layer slurry prepared using the aforementioned preparation method.
[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. Suppressing excessive competitive adsorption of ionomers: By pre-mixing the solvent evenly and dividing it into two parts in different proportions, one for pre-dispersing the catalyst and the other for pre-dispersing the ionomer, the solvent environment of the two dispersions is ensured to be completely consistent. This allows the ionomers to expand and detangle in the final solvent system before mixing, avoiding excessive contact with the catalyst surface in the early stages of catalyst dispersion. This suppresses uneven coating of the ionomers on the outer surface of the catalyst, which is conducive to the formation of a more uniform ion transport network.
[0021] 2. Significantly Improved Slurry Dispersion Stability: Pre-dispersing the catalyst in a premixed solvent identical to the final slurry solvent significantly enhances its initial dispersion state and effectively prevents catalyst particle agglomeration. Similarly, pre-diluting the ionomer in the same solvent allows its molecular chains to fully extend, forming stable micelles. This stepwise pretreatment ensures that both the catalyst and ionomer reach their optimal initial dispersion states. Combined with high-speed shearing, this results in a small average particle size and narrow distribution in the slurry, with almost no change in particle size after 72 hours of standing, far superior to the comparative example. This characteristic is beneficial for improving coating stability and batch consistency.
[0022] 3. Significantly Improved Catalytic Layer Performance: The slurry prepared using this method promotes the formation of a uniform and complete ionomer / catalyst interface on the catalyst surface, which helps to construct a uniform microstructure of the catalytic layer. This, in turn, optimizes the three-phase reaction interface and improves catalyst utilization and proton conductivity. Attached Figure Description
[0023] Figure 1The graph shows a comparison of the polarization curves of single cells prepared from the catalytic layer slurries obtained in Examples 1-4 and Comparative Examples 1-2 under 70% relative humidity (RH). Detailed Implementation
[0024] Example 1 1. Mix deionized water and n-propanol at a mass ratio of 1:3 and stir until homogeneous to obtain a mixed solvent.
[0025] 2. Take 33 g of mixed solvent and divide it into two portions of 16.5 g each, in a 1:1 mass ratio.
[0026] 3. Take 0.5 g of Pt / C catalyst (60wt% Pt), add it to the first mixed solvent, and ultrasonically disperse it for 10 min under a water bath at 25℃ to obtain the catalyst dispersion.
[0027] 4. Based on a mass ratio of ionomer dry weight to carbon support in the catalyst of 0.95:1, take 0.95 g of ionomer solution (Nafion). TM D2020 perfluorosulfonic acid resin dispersion (20wt%) was added to the second mixed solvent and ultrasonically dispersed for 10 min in a water bath at 25°C to obtain an ionomer dispersion.
[0028] 5. Under magnetic stirring at 500 rpm, slowly add the ionomer dispersion to the catalyst dispersion, and continue stirring for 60 min after the addition is complete.
[0029] 6. Transfer the premixed slurry to a high shear disperser (model IKA T25) and disperse it for 60 min under shear linear velocity of 25 m / s and ice-water bath cooling conditions (temperature controlled at 5~10℃) to obtain the final catalyst layer slurry.
[0030] Example 2 1. Mix deionized water and isopropanol at a mass ratio of 5:1 and stir until homogeneous to obtain a mixed solvent.
[0031] 2. Take 32.6 g of mixed solvent and divide it into two portions of 8.15 g and 24.45 g by mass ratio of 1:3.
[0032] 3. Take 0.5 g of Pt / C catalyst (60wt% Pt), add it to the first mixed solvent, and ultrasonically disperse it for 30 min under a water bath at 25℃ to obtain the catalyst dispersion.
[0033] 4. Based on a mass ratio of ionomer dry weight to carbon support in the catalyst of 1.2:1, take 1.2 g of ionomer solution (Nafion). TMD2020 perfluorosulfonic acid resin dispersion (20wt%) was added to the second mixed solvent and ultrasonically dispersed for 30 min in a water bath at 25°C to obtain an ionomer dispersion.
[0034] 5. Under magnetic stirring at 500 rpm, add the ionomer dispersion to the catalyst dispersion in one go, and continue stirring for 10 min after the addition is complete.
[0035] 6. Transfer the premixed slurry to a high shear disperser (model IKA T25) and disperse it for 30 min under shear linear velocity of 10 m / s and ice-water bath cooling conditions (temperature controlled at 5~10℃) to obtain the final catalyst layer slurry.
[0036] Example 3 1. Mix deionized water and n-propanol at a mass ratio of 2:1 and stir until homogeneous to obtain a mixed solvent.
[0037] 2. Take 33 g of mixed solvent and divide it into two portions of 10 g and 20 g by mass ratio of 1:2.
[0038] 3. Take 0.5 g of Pt / C catalyst (60wt% Pt), add it to the first mixed solvent, and ultrasonically disperse it for 30 min under a 5℃ water bath to obtain the catalyst dispersion.
[0039] 4. Based on a mass ratio of ionomer dry weight to carbon support in the catalyst of 0.95:1, take 0.95 g of ionomer solution (Nafion). TM D2020 perfluorosulfonic acid resin dispersion (20wt%) was added to the second mixed solvent and ultrasonically dispersed for 30 min in a 5℃ water bath to obtain an ionomer dispersion.
[0040] 5. Under magnetic stirring at 500 rpm, slowly add the ionomer dispersion to the catalyst dispersion, and continue stirring for 50 min after the addition is complete.
[0041] 6. Transfer the premixed slurry to a high shear disperser (model IKA T25) and disperse it for 40 min under shear linear velocity of 25 m / s and ice-water bath cooling conditions (temperature controlled at 5~10℃) to obtain the final catalyst layer slurry.
[0042] Example 4 1. Mix deionized water and n-propanol at a mass ratio of 2:1 and stir until homogeneous to obtain a mixed solvent.
[0043] 2. Take 33 g of mixed solvent and divide it into two portions of 10 g and 20 g by mass ratio of 1:2.
[0044] 3. Take 0.5 g of Pt / C catalyst (50wt% Pt), add it to the first mixed solvent, and ultrasonically disperse it for 30 min under a water bath at 5℃ to obtain the catalyst dispersion.
[0045] 4. Based on a mass ratio of ionomer dry weight to carbon support in the catalyst of 0.8:1, take 1 g of ionomer solution (Nafion) TM D2020 perfluorosulfonic acid resin dispersion (20wt%) was added to the second mixed solvent and ultrasonically dispersed for 30 min in a 5℃ water bath to obtain an ionomer dispersion.
[0046] 5. Under magnetic stirring at 500 rpm, slowly add the ionomer dispersion to the catalyst dispersion, and continue stirring for 50 min after the addition is complete.
[0047] 6. Transfer the premixed slurry to a high shear disperser (model IKA T25) and disperse it for 40 min under shear linear velocity of 25 m / s and ice-water bath cooling conditions (temperature controlled at 5~10℃) to obtain the final catalyst layer slurry.
[0048] Comparative Example 1 1. Add 33 g of mixed solvent (deionized water and n-propanol in a mass ratio of 1:3) and 0.95 g of ionomer solution (D2020 perfluorosulfonic acid resin dispersion, 20wt%) to 0.5 g of Pt / C catalyst (60wt% Pt) in sequence. After mixing in one go, place the mixture in an ultrasonic disperser and sonicate for 10 min at a controlled temperature of 25℃ in an ice-water bath.
[0049] 2. Using a high-shear disperser (model IKA T25) at a linear speed of 25 m / s, the dispersion was carried out in an ice-water bath for 60 min to obtain the catalyst layer slurry.
[0050] Comparative Example 2 1. Take 0.5 g of Pt / C catalyst (60wt% Pt), add 8.1 g of deionized water, and ultrasonically disperse for 10 min under a water bath at 25℃ to obtain a catalyst dispersion.
[0051] 2. Take 0.95 g of ionomer solution (D2020 dispersion, 20wt%), add 24.9 g of n-propanol, and ultrasonically disperse for 10 min under a water bath at 25℃ to obtain ionomer dispersion.
[0052] 3. Under magnetic stirring at 500 rpm, the ionomer dispersion is added dropwise to the catalyst dispersion, and stirring is continued for 10 min after the addition is complete.
[0053] 4. Transfer the premixed slurry to a high shear disperser (model IKA T25) and disperse it for 60 min under shear linear velocity of 25 m / s and ice-water bath cooling conditions to obtain the final catalyst layer slurry.
[0054] Detection Example 1 The initial D50 and D90 values of the slurries obtained in each example and comparative example were determined using a laser particle size analyzer, and the D50 and D90 values of each group were determined again after standing at room temperature for 72 hours. The settling time was determined by testing the change in slurry particle size (the change in particle size before and after standing was < 2%).
[0055] Table 1 The results are shown in Table 1. The slurry prepared in the embodiments of the present invention has a smaller initial particle size (D50 < 0.8 μm) and almost no particle size growth after standing for 72 h, exhibiting excellent dispersion stability. In contrast, the slurry of Comparative Example 1 not only has a larger initial particle size but also exhibits severe agglomeration after standing. Although Comparative Example 2 uses stepwise dispersion, the catalyst and ionomer are dispersed in different single solvents (water and n-propanol, respectively), resulting in a sudden change in the solvent environment after mixing, leading to a larger particle size than in the embodiments and poorer stability.
[0056] Detection Example 2 Single-cell testing: The slurries from the examples and comparative examples were prepared into CCM (catalyst-coated films) by spraying, with a cathode Pt loading of 0.35 mg / cm³. 2 Anode Pt loading 0.05 mg / cm³ 2 Assemble single cells and test polarization curves under conditions of 80°C, 50 kPa back pressure and 70% relative humidity (RH).
[0057] Table 2 The results are as follows Figure 1 As shown in Table 2, at 2000 mA / cm 2 Under electrical density conditions, the single-cell voltage corresponding to Example 1 is 0.648V, and that of Comparative Example 2 is 0.635V. This indicates that the catalyst layer formed by the slurry prepared by the method of the present invention has a better three-phase reaction interface and lower ion transport resistance, thus improving the battery performance to a certain extent.
Claims
1. A method for preparing a slurry for a fuel cell membrane electrode catalytic layer, characterized in that, Includes the following steps: Step 1: Prepare a mixed solvent system; Step 2: Divide the mixed solvent system obtained in Step 1 into a first mixed solvent and a second mixed solvent by mass ratio; Step 3: Add the platinum-based catalyst to the first mixed solvent described in Step 2 and perform a first dispersion treatment to obtain a catalyst dispersion. Step 4: Add the ionomer to the second mixed solvent described in Step 2 and perform a second dispersion treatment to obtain an ionomer dispersion. Step 5: Under stirring conditions, add the ionomer dispersion obtained in step 4 to the catalyst dispersion obtained in step 3, mix evenly, and obtain a premixed slurry. Step 6: The premixed slurry obtained in step 5 is subjected to shear dispersion treatment to obtain the fuel cell membrane electrode catalyst layer slurry.
2. The preparation method according to claim 1, characterized in that, In step 1, deionized water and alcohol solvent are mixed at a mass ratio of 1:3 to 5:1 to obtain the mixed solvent system; the alcohol solvent is selected from one or more of ethanol, isopropanol, and n-propanol.
3. The preparation method according to claim 1, characterized in that, In step 2, the mass ratio of the first mixed solvent to the second mixed solvent is 1:1 to 1:
3.
4. The preparation method according to claim 1, characterized in that, The platinum-based catalyst mentioned in step 3 is a platinum-carbon catalyst.
5. The preparation method according to claim 1, characterized in that, The ionomer mentioned in step 4 is a perfluorosulfonic acid resin.
6. The preparation method according to claim 1, characterized in that, Step 3: The first dispersion treatment uses ultrasonic dispersion for 10-30 min at a temperature of 5-25℃; Step 4: The second dispersion treatment uses ultrasonic dispersion for 10-30 min at a temperature of 5-25℃.
7. The preparation method according to claim 1, characterized in that, The stirring conditions described in step 5 are magnetic stirring at a speed of 500 rpm.
8. The preparation method according to claim 1, characterized in that, The ionomer dispersion in step 5 is added dropwise or all at once; the time for mixing evenly is 10-60 min.
9. The preparation method according to claim 1, characterized in that, The high-speed shear dispersion described in step 6 uses a high-speed shear dispersion machine with a shearing linear velocity of 10~25 m / s, a processing time of 30~60 min, and a slurry temperature of 5~10℃.
10. A slurry for the catalyst layer of a fuel cell membrane electrode, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
A self-humidifying fuel cell membrane electrode and preparation method thereof
CN116454290B
Fuel cell catalyst layer and preparation method thereof
CN121662835A